Kinerja Perangkat Desa dalam Pelayanan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB –P2) di Wilayah Kecamatan Pagerbarang Kabupaten Tegal - Munanto, Munanto (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2022)
Land and Building Tax (PBB) which is used to finance the administration of government and regional development to the village level. Optimizing PBB Revenue is expected to be able to increase regional revenue revenues, including increasing development in the village. The problems that occur can not be separated from the Performance of the Village Apparatus in service. The purpose of this study was to determine the performance of the village apparatus, the constraints of the village government, and solutions to overcome obstacles in the service of the PBB. The results showed that the performance of PBB services was quite good, but not yet optimal. Of the 13 (thirteen) villages in Pagerbarang Subdistrict when the due date of September 30 each year there are always villages that have not reached the 100% realization target. This performance improvement effort is needed by involving all components. The sub-district often motivates the Village Head and Village Apparatus to be even more active in increasing the realization of PBB acquisition in their respective villages. The punishment and reward system is also considered effective in improving the performance of village officials. Constraints experienced by the Village Government in providing PBB services are the lack of village apparatus, the low quality of village apparatus human resources, the relatively large amount of time the workload of village officials, rewards in the form of profit sharing incentives are still low and punishments are still light. for village officials who violate the rules. Solutions to overcome obstacles in UN services include the need for intensive guidance from the sub-district and district, the need for training/instruction for improving skills and knowledge of village officials, compensation system in the form of adequate PBB profit sharing, conducive work climate , Village Government organizational strategy, Support of quality human resources of village officials and village heads, as well as good management of village government. Keywords: Performance, PBB, Village Government